A guide to the tadpoles of Borneo - Alexander Haas; Indraneil Das; Stefan T. Hertwig; Pia Bublies; Reinhard Schulz-Schaeffer (2022)
Tadpoles are an important, albeit often neglected, part of the life-cycle of frogs. These larval forms play a critical role in the ecology of aquatic habitats. Their morpho- logical and ecological diversity is remarkable, although comprehensive inventories and descriptions of the tadpole fauna are unavailable for most regions of the world. This book presents tadpole descriptions for 99 species from the southeast Asian island of Borneo, covering all species commonly found, as well as representatives of the more cryptic ones. These are typically depicted from life with color photographs, mostly for the first time. The aims of this book are to allow a broad audi- ence an easy access to the tadpole fauna of Borneo, increase awareness of these life stages, document their diversity, and provide insights into their fascinating biology.
Keywords: Biologie; Wissenschaftsillustration; Wissenschaftskommunikation